Coating material for balsa wood surface treatment and treatment process

By using coating materials in wind power blades, including polyurethane resin, epoxy resin and Cu2O/ZnO composite particle inorganic photoinitiator, the UV curing coating on the surface of light wood is solved, and the problem of light wood absorbing too much resin in the infused resin is achieved, achieving better adhesion and durability.

CN119570353AInactive Publication Date: 2025-03-07GURIT (TIANJIN) COMPOSITE MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411535062.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the production process of wind power blades, light wood tends to absorb too much resin when infusing resin, resulting in whitening and layering problems.

Method used

A coating material for surface treatment of light wood is adopted, which includes polyurethane resin, epoxy resin, Cu2O/ZnO composite particle inorganic photoinitiator, lauryl acrylate and tripropylene glycol diacrylate. The coating is formed by UV irradiation to protect light wood and reduce its absorption of the infused resin.

Benefits of technology

It effectively reduces the amount of glue absorption of light wood, improves the adhesion, water resistance and alkali resistance of the coating, and avoids the occurrence of whitening and stratification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of balsa wood surface treatment, in particular to a coating material for balsa wood surface treatment and a treatment process. The coating material for balsa wood surface treatment comprises the following raw materials in parts by weight: 50-90 parts of polyurethane resin, 45-80 parts of epoxy resin, 5-15 parts of a photoinitiator, 1-3 parts of lauryl acrylate and 1-3 parts of tripropylene glycol diacrylate. The photoinitiator is a Cu2O / ZnO composite particle inorganic photoinitiator. The balsa wood surface treatment process comprises the following steps that S1, balsa wood is subjected to surface dull polish treatment; s2, dust removal is conducted on the surface of the balsa wood subjected to frosted treatment; s3, the surface of the balsa wood is coated with a coating material through a gumming machine, wherein the coating material is any one of the coating materials for balsa wood surface treatment according to claims 1-8; and S4, the cork wood coated with the coating material is subjected to UV drying treatment. The glue absorption amount of the obtained balsa wood can be as low as 1.00 kg / m < 3 >, the adhesive force grade of a coating on the surface of the balsa wood can reach 0 grade, and the water resistance and alkali resistance are excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of balsa wood surface treatment, and in particular to a coating material and a treatment process for balsa wood surface treatment. Background Art

[0002] As a renewable energy, wind power generation is a new energy source different from traditional energy sources. Compared with other new energy sources such as solar power generation, wind power generation has more scale and economic advantages.

[0003] The upstream materials of the wind power industry mainly include towers, wind turbines, nacelles, main shafts, cables and blades. Wind turbine blades are one of the core components of wind turbines. Their good design, reliable quality and superior performance are the decisive factors to ensure the normal and stable operation of wind turbines.

[0004] From the perspective of wind turbine blade structure, it is mainly composed of reinforcement materials, sandwich materials, matrix materials, surface coatings and structural adhesives between different parts. In the application of wind turbine blades, the structural core material is the key material of wind turbine blades. The sandwich materials currently used in wind turbine blades mainly include balsa wood, PVC foam, PET foam, etc. Among them, balsa wood has a light texture, a strong structure, low density, high strength, sound insulation, heat insulation and other properties, and is usually used in the root of the blade.

[0005] When producing wind turbine blades, after installing the balsa wood, it is necessary to inject resin and other materials to finally form a core material with a sandwich structure.

[0006] With respect to the above-mentioned related technologies, the applicant has found that balsa wood will absorb resin when being infused with resin, and excessive absorption of resin will lead to whitening, delamination and other phenomena. Summary of the invention

[0007] In order to reduce the amount of glue absorbed by balsa wood, the present application provides a coating material and a treatment process for balsa wood surface treatment.

[0008] In a first aspect, the present application provides a coating material for balsa wood surface treatment, which adopts the following technical solution.

[0009] A coating material for balsa wood surface treatment comprises the following raw materials in parts by weight: 50-90 parts of polyurethane resin, 45-80 parts of epoxy resin, 5-15 parts of photoinitiator, 1-3 parts of lauryl acrylate, and 1-3 parts of tripropylene glycol diacrylate; The photoinitiator is a Cu2O / ZnO composite particle inorganic photoinitiator.

[0010] By adopting the above technical scheme, polyurethane resin and epoxy resin are used as photocuring resins, Cu2O / ZnO composite particles are used as photoinitiators, lauryl acrylate and tripropylene glycol diacrylate are used to adjust the overall viscosity of the material, and a coating is formed after UV irradiation to protect the balsa wood and reduce the absorption of the balsa wood by the infusion resin.

[0011] Nano zinc oxide is an important optoelectronic semiconductor material. It has a wide energy band and large exciton binding energy at room temperature, strong ultraviolet light absorption ability, wide radiation absorption range and high photostability, and can be used as a photoinitiator. However, nano zinc oxide is not well used as a photoinitiator due to its low photocuring conversion rate. Copper oxide has a high absorption coefficient and photoelectric conversion efficiency in the visible light region. Nano zinc oxide is modified by copper oxide according to the principle of energy level position matching, and the resulting composite particles have good photoinitiation efficiency. The addition of copper oxide expands the light absorption range of nano zinc oxide photoinitiator from the ultraviolet light region to the visible light region, which greatly improves the utilization rate of light. In addition, the interaction between copper oxide and zinc oxide particles also makes the mechanical properties of the obtained coating more excellent. Finally, the adsorption and migration behavior of small molecules in the photocurable film is controlled by the morphology of the photocurable film and the macromolecular network structure. Nanoparticles can enhance the macromolecular network structure in amorphous and crystalline polymers. Using composite particles as photoinitiators can also improve the water resistance and alkali resistance of the coating.

[0012] Furthermore, the preparation method of the Cu2O / ZnO composite particle inorganic photoinitiator is: 1. Disperse zinc oxide and copper acetate in anhydrous ethanol to obtain a mixed dispersion; 2. Add glacial acetic acid dropwise to the mixed dispersion, raise the temperature to 55-65°C, react for 0.5h, and obtain a reaction base liquid; 3. Maintaining the temperature, add glucose solution, sodium hydroxide solution, distilled water and anhydrous ethanol to the reaction base liquid in sequence, and react for 25-35 minutes after the addition is completed to obtain a reaction product; 4. Filter the reaction product, retain the solid, wash and dry the solid to obtain a Cu2O / ZnO composite particle inorganic photoinitiator.

[0013] Furthermore, the weight ratio of zinc oxide to cupric acetate is: 1:(1-1.5).

[0014] By adopting the above technical solution, the ratio of zinc oxide to copper acetate is limited, that is, the ratio of zinc oxide to copper oxide is limited, so that the comprehensive effect of the photoinitiator in photoinitiation and improvement of coating performance is better.

[0015] Furthermore, the weight ratio of the copper acetate, glucose and sodium hydroxide is 1:(2.5-3.5):(3.5-5.0) based on the glucose in the glucose solution and the sodium hydroxide in the sodium hydroxide solution.

[0016] Furthermore, the dropping speed of the glucose solution, sodium hydroxide solution, distilled water and anhydrous ethanol is 13-14 ml / min.

[0017] Furthermore, the concentration of the glucose solution is 0.04 kg / L, and the concentration of the sodium hydroxide solution is 0.05 kg / L.

[0018] Furthermore, the preparation method of the polyurethane resin is: a. Under the action of protective gas, isophorone diisocyanate and 2,2-dimethylol propionic acid are dissolved in a solvent to obtain an isophorone diisocyanate solution and a 2,2-dimethylol propionic acid solution, and then the 2,2-dimethylol propionic acid solution is added dropwise to the isophorone diisocyanate solution, and the reaction is carried out at 60-70° C. for 35-45 min. After the reaction is completed, the temperature is lowered to 25-30° C., diethanolamine is added, and the reaction is carried out for 80-100 min, and then the temperature is raised to 80-90° C. and the reaction is carried out for 5 h to obtain a polyhydroxy hyperbranched monomer; b. Under the action of protective gas, diphenylmethane diisocyanate is dissolved in butanone to obtain a diphenylmethane diisocyanate solution, and polytetrahydrofuran is added dropwise after the temperature is raised to 60-70°C, and the reaction is carried out for 2 hours; after the reaction is completed, butanediol is added and the reaction is continued for 3 hours; after the reaction is completed, the polyhydroxy hyperbranched monomer obtained in a and hydroxyethyl methacrylate are added, and the reaction is carried out for 2 hours to obtain a polyurethane resin.

[0019] Furthermore, the weight ratio of isophorone diisocyanate to diphenylmethane diisocyanate is (0.6-0.9):1.

[0020] By adopting the above technical scheme, a polyhydroxy hyperbranched monomer structure is first synthesized using isophorone diisocyanate, and then this monomer structure is introduced into a polyurethane system prepared by diphenylmethane diisocyanate to obtain the polyurethane resin containing a hyperbranched structure of the present application. The obtained polyurethane resin contains a large number of functional groups, which greatly improves the bonding strength between the coating and the balsa wood.

[0021] In a second aspect, the present application provides a balsa wood surface treatment process, which adopts the following technical solution.

[0022] A balsa wood surface treatment process comprises the following steps: S1. Surface frosting of balsa wood; S2. Remove dust from the frosted balsa wood surface; S3. Coating the coating material on the balsa wood surface with a glue coater, wherein the coating material is a balsa wood surface treatment coating material according to any one of claims 1-8; S4. The balsa wood coated with the coating material is subjected to UV drying treatment.

[0023] In summary, this application has the following beneficial effects: This application uses polyurethane resin and epoxy resin as light-curing resin, Cu2O / ZnO composite particles as photoinitiator, lauryl acrylate and tripropylene glycol diacrylate to adjust the viscosity of the whole material, and forms a coating after UV irradiation to protect the balsa wood and reduce the absorption of the balsa wood to the infusion resin. The glue absorption of the obtained balsa wood can be as low as 1.00kg / m 3 , and the coating adhesion level on the balsa wood surface can reach level 0, and it has excellent water and alkali resistance. DETAILED DESCRIPTION

[0024] The present application is further described in detail below with reference to the embodiments.

[0025] Raw materials and intermediate preparation examples raw material Epoxy resin, E51; Lauryl acrylate, technical grade; Tripropylene glycol diacrylate, technical grade; Zinc oxide, 40-50nm; Cupric acetate, analytical grade; Glacial acetic acid, analytical grade; Glucose, anhydrous glucose, analytical grade; Isophorone diisocyanate, analytical grade; 2,2-Dihydroxymethylpropionic acid, analytical grade; Solvent, N,N-dimethylformamide, analytical grade; Diethanolamine, analytical grade; Diphenylmethane diisocyanate, analytical grade; Butanone, analytical grade; Polytetrahydrofuran, analytical grade; Butanediol, analytical grade; Hydroxyethyl methacrylate, analytical grade; Polyurethane resin, commercially available polyurethane acrylic resin for light-curing adhesive, brand name HD-100.

[0026] Preparation Example Preparation Example 1 A Cu2O / ZnO composite particle inorganic photoinitiator, the preparation method of which is as follows: 1. Add 1 kg zinc oxide and 1.2 kg copper acetate into 100 L anhydrous ethanol and disperse by ultrasonic for 30 min to obtain a mixed dispersion; 2. Add 4L of glacial acetic acid to the mixed dispersion, raise the temperature to 60°C, react for 0.5h, remove bound water, and obtain a reaction base liquid; 3. Maintaining the temperature, add glucose solution, sodium hydroxide solution, distilled water and anhydrous ethanol to the reaction base liquid in sequence at a dropping speed of 13 ml / min. After the addition is completed, react for 30 minutes to obtain a reaction product; Glucose solution: Dissolve 3.6 kg of glucose in 90 L of water to obtain a glucose solution with a concentration of 0.04 kg / L; Sodium hydroxide solution: Dissolve 5.4 kg of sodium hydroxide in 108 L of water to obtain a sodium hydroxide solution with a concentration of 0.05 kg / L; Distilled water: 50L; Anhydrous ethanol: 70L; 4. The reaction product was filtered, and the solid was retained. The solid was washed with water and anhydrous ethanol for 3 times each, and then vacuum dried at 60° C. for 12 h to obtain a Cu2O / ZnO composite particle inorganic photoinitiator.

[0027] Preparation Example 2 The difference from Preparation Example 1 is that the amount of copper acetate used in Preparation Example 2 is 1 kg. Glucose solution: 3 kg of glucose is dissolved in 75 L of water to obtain a glucose solution with a concentration of 0.04 kg / L; sodium hydroxide solution: 4.5 kg of sodium hydroxide is dissolved in 90 L of water to obtain a sodium hydroxide solution with a concentration of 0.05 kg / L.

[0028] Preparation Example 3 Different from Preparation Example 1, the amount of copper acetate used in Preparation Example 3 is 1.5 kg. Glucose solution: 4.5 kg of glucose is dissolved in 112.5 L of water to obtain a glucose solution with a concentration of 0.04 kg / L; sodium hydroxide solution: 6.75 kg of sodium hydroxide is dissolved in 135 L of water to obtain a sodium hydroxide solution with a concentration of 0.05 kg / L.

[0029] Preparation Example 4 Different from Preparation Example 1, the amount of copper acetate used in Preparation Example 4 is 2 kg. Glucose solution: 6 kg of glucose is dissolved in 150 L of water to obtain a glucose solution with a concentration of 0.04 kg / L; sodium hydroxide solution: 9 kg of sodium hydroxide is dissolved in 180 L of water to obtain a sodium hydroxide solution with a concentration of 0.05 kg / L.

[0030] Preparation Example 5 Different from Preparation Example 1, in Preparation Example 5, the glucose solution is as follows: 3 kg of glucose is dissolved in 75 L of water to obtain a glucose solution with a concentration of 0.04 kg / L; the sodium hydroxide solution is as follows: 6 kg of sodium hydroxide is dissolved in 120 L of water to obtain a sodium hydroxide solution with a concentration of 0.05 kg / L.

[0031] Preparation Example 6 Different from Preparation Example 1, in Preparation Example 6, the glucose solution is as follows: 4.2 kg of glucose is dissolved in 105 L of water to obtain a glucose solution with a concentration of 0.04 kg / L; the sodium hydroxide solution is as follows: 4.2 kg of sodium hydroxide is dissolved in 84 L of water to obtain a sodium hydroxide solution with a concentration of 0.05 kg / L.

[0032] Preparation Example 7 A polyurethane resin, the preparation method of which is as follows: a. Under the protection of nitrogen, 0.6 kg of isophorone diisocyanate and 0.02 kg of 2,2-dimethylol propionic acid were dissolved in a solvent to obtain an isophorone diisocyanate solution and a 2,2-dimethylol propionic acid solution, and then the 2,2-dimethylol propionic acid solution was added dropwise to the isophorone diisocyanate solution, and the reaction was carried out at 65 ° C for 40 min. After the reaction was completed, the temperature was lowered to 25 ° C, 0.02 kg of diethanolamine was added and reacted for 90 min, and then the temperature was raised to 85 ° C and reacted for 5 h to obtain a polyhydroxy hyperbranched monomer; b. Under the protection of nitrogen, 1 kg of diphenylmethane diisocyanate was dissolved in butanone to obtain a diphenylmethane diisocyanate solution, and 4 kg of polytetrahydrofuran was added dropwise after the temperature was raised to 65°C, and the reaction was continued for 2 hours; after the reaction, 0.2 kg of butanediol was added and the reaction was continued for 3 hours; after the reaction, the polyhydroxy hyperbranched monomer obtained in a and 0.06 kg of hydroxyethyl methacrylate were added, and the reaction was continued for 2 hours to obtain a polyurethane resin.

[0033] Preparation Example 8 Different from Preparation Example 7, the amount of isophorone diisocyanate used in Preparation Example 8 is 0.9 kg.

[0034] Preparation Example 9 Different from Preparation Example 7, the amount of isophorone diisocyanate used in Preparation Example 9 is 1.1 kg.

[0035] Example

[0036] Example 1 A coating material for balsa wood surface treatment, and a preparation method thereof is as follows: The raw materials were mixed evenly according to the raw material ratio in Table 1, and packaged to obtain the coating material for balsa wood surface treatment.

[0037] Table 1 Raw material ratio table (kg)

[0038] Wherein, the polyurethane resin comes from Preparation Example 7, and the photoinitiator comes from Preparation Example 1.

[0039] Embodiment 4-8 Different from Example 2, the photoinitiators in Examples 4-8 are from Preparation Examples 2-6, respectively.

[0040] Examples 9-10 Different from Example 2, the polyurethanes in Examples 9-10 are respectively from Preparation Examples 8-9.

[0041] Embodiment 11 Different from Example 2, the polyurethane in Example 11 is a commercially available polyurethane acrylic resin specially used for photocurable adhesives.

[0042] Comparative Example Comparative Example 1 Different from Example 1, the photoinitiator in Comparative Example 1 is 2-hydroxy-2-methylpropiophenone.

[0043] Comparative Example 2 Different from Example 1, the photoinitiator in Comparative Example 2 is nano zinc oxide.

[0044] Comparative Example 3 Different from Example 1, the photoinitiator in Comparative Example 3 is nano copper oxide.

[0045] Application Examples Application Example 1 A balsa wood surface treatment process comprises the following steps: S1. Surface sanding of balsa wood Use a sander to sand the balsa wood surface. Use 100-grit sandpaper for sanding regular balsa wood sheets, and use 40-grit sandpaper for sanding the top and bottom sheets of the wood squares. S2. Dust removal on frosted balsa wood surfaces Use a dust collector to remove impurities from the balsa wood surface; S3. Apply the coating material to the balsa wood surface with a glue coating machine Turn on the glue coating machine, turn on the resin heater three hours in advance, set the temperature to 80°C, put a plastic bag inside the resin heater, add the coating material obtained in Example 1, stir with a stirrer, and after the resin temperature rises, put the suction head into the heater, turn on the glue suction pump to start feeding glue, adjust the valve on the pump to control the amount of glue, turn on the steel roller and rubber roller to circulate and feed glue for half an hour, adjust the appropriate height according to the thickness of the plate, adjust the distance between the steel roller and the rubber roller, adjust the speed of the rubber roller and the steel roller, then the resin starts to circulate, and you can start feeding the plate and applying glue; S4. UV drying of the balsa wood coated with the coating material Turn on the UV dryer, turn on the switch, turn on the conveyor belt, adjust the conveyor belt speed and turn on the light, turn on half the light and pause for 5 seconds, then turn on the full light.

[0046] Application Example 2-11 Different from Application Example 1, the coating materials in Application Examples 2-11 are respectively from Embodiments 2-11.

[0047] Comparative Application Examples Comparative Application Examples 1-3 Different from Application Example 1, the coating materials in the comparative application examples come from Comparative Examples 1-3 respectively.

[0048] Performance Testing The glue absorption performance (resin absorption amount) of balsa wood obtained in the corresponding use cases of TR-7323 and the comparative application examples was tested, and the test results are shown in Table 2.

[0049] Coating specimens were prepared according to the methods in the application examples and comparative application examples for coating performance testing: the coating adhesion was tested with reference to GB / T9286-2021, the coating water resistance was tested with reference to GB / T 1733-1993, and the coating alkali resistance was tested with reference to GB / T 9265-2009. The test results are shown in Table 2.

[0050] Table 2 Performance test results

[0051] Combining Application Examples 1-11 with Comparative Application Examples 1-3, and in combination with Table 2, it can be seen that the amount of glue absorbed by the balsa wood obtained in Application Examples 1-11 is significantly lower than that in Comparative Application Examples 1-3; and the adhesion, water resistance and alkali resistance of the coating obtained in Comparative Application Examples 1-11 are better than those in Comparative Application Examples 1-3. This may be because the comprehensive performance of the coating obtained in the present application is better, thereby providing more comprehensive protection for the balsa wood and reducing the amount of glue absorbed by the balsa wood.

[0052] Combining Application Example 1 with Comparative Application Example 1 and Table 2, it can be seen that the amount of glue absorbed by the balsa wood obtained in Application Example 1 is significantly lower than that in Comparative Application Example 1; and the adhesion, water resistance and alkali resistance of the coating obtained in Comparative Application Example 1 are better than those in Comparative Application Example 1; this shows that the overall performance of the photocurable coating obtained using Cu2O / ZnO composite particles as a photoinitiator is better than that of the photocurable coating obtained using 2-hydroxy-2-methylpropiophenone as an initiator. This may be because the nano zinc oxide is modified by copper oxide through the principle of energy level position matching, and the obtained composite particles have good photoinitiation efficiency. The addition of copper oxide expands the light absorption range of the nano zinc oxide photoinitiator from the ultraviolet light region to the visible light region, which greatly improves the utilization rate of light. In addition, the interaction between the two particles of copper oxide and zinc oxide also makes the mechanical properties of the obtained coating more excellent. Finally, the adsorption and migration behavior of small molecules in photocured films are controlled by the morphology of the photocured films and the macromolecular network structure. Nanoparticles can enhance the macromolecular network structure in amorphous and crystalline polymers. Using composite particles as photoinitiators can also improve the comprehensive performance of the coating.

[0053] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A coating material for balsa wood surface treatment, characterized in that: The method comprises the following raw materials in parts by weight: 50-90 parts of polyurethane resin, 45-80 parts of epoxy resin, 5-15 parts of photoinitiator, 1-3 parts of lauryl acrylate, and 1-3 parts of tripropylene glycol diacrylate; The photoinitiator is a Cu2O / ZnO composite particle inorganic photoinitiator.

2. The coating material for balsa wood surface treatment according to claim 1, characterized in that: The preparation method of the Cu2O / ZnO composite particle inorganic photoinitiator is:

1. Disperse zinc oxide and copper acetate in anhydrous ethanol to obtain a mixed dispersion; 2. Add glacial acetic acid to the mixed dispersion, raise the temperature to 55-65°C, react for 0.5h, and obtain a reaction base liquid; 3. Maintaining the temperature, add glucose solution, sodium hydroxide solution, distilled water and anhydrous ethanol to the reaction base liquid in sequence, and react for 25-35 minutes after the addition is completed to obtain a reaction product; 4. Filter the reaction product, retain the solid, wash and dry the solid to obtain a Cu2O / ZnO composite particle inorganic photoinitiator.

3. The coating material for balsa wood surface treatment according to claim 2, characterized in that: The weight ratio of zinc oxide to cupric acetate is: 1:(1-1.5).

4. The coating material for balsa wood surface treatment according to claim 2, characterized in that: Calculated based on the glucose in the glucose solution and the sodium hydroxide in the sodium hydroxide solution, the weight ratio of the copper acetate, glucose and sodium hydroxide is 1:(2.5-3.5):(3.5-5.0).

5. The coating material for balsa wood surface treatment according to claim 2, characterized in that: The dropping speed of the glucose solution, sodium hydroxide solution, distilled water and anhydrous ethanol is 13-14 ml / min.

6. The coating material for balsa wood surface treatment according to claim 2, characterized in that: The concentration of the glucose solution is 0.04 kg / L, and the concentration of the sodium hydroxide solution is 0.05 kg / L.

7. The coating material for balsa wood surface treatment according to claim 1, characterized in that: The preparation method of the polyurethane resin is: a. Under the action of protective gas, isophorone diisocyanate and 2,2-dimethylol propionic acid are dissolved in a solvent to obtain an isophorone diisocyanate solution and a 2,2-dimethylol propionic acid solution, and then the 2,2-dimethylol propionic acid solution is added dropwise to the isophorone diisocyanate solution, and the reaction is carried out at 60-70° C. for 35-45 min. After the reaction is completed, the temperature is lowered to 25-30° C., diethanolamine is added, and the reaction is carried out for 80-100 min, and then the temperature is raised to 80-90° C. and the reaction is carried out for 5 h to obtain a polyhydroxy hyperbranched monomer; b. Under the action of protective gas, diphenylmethane diisocyanate is dissolved in butanone to obtain a diphenylmethane diisocyanate solution, and polytetrahydrofuran is added dropwise after the temperature is raised to 60-70°C, and the reaction is carried out for 2 hours; after the reaction is completed, butanediol is added and the reaction is continued for 3 hours; after the reaction is completed, the polyhydroxy hyperbranched monomer obtained in a and hydroxyethyl methacrylate are added, and the reaction is carried out for 2 hours to obtain a polyurethane resin.

8. The coating material for balsa wood surface treatment according to claim 7, characterized in that: The weight ratio of isophorone diisocyanate to diphenylmethane diisocyanate is (0.6-0.9):

1.

9. A balsa wood surface treatment process, characterized in that: The following steps are involved: S1. Surface sanding of balsa wood; S2. Remove dust from the frosted balsa wood surface; S3. Coating the coating material on the balsa wood surface with a glue coater, wherein the coating material is a balsa wood surface treatment coating material according to any one of claims 1-8; S4. The balsa wood coated with the coating material is subjected to UV drying treatment.